Surface passivation method for improving corrosion resistance of low-chromium ferritic stainless steel for highway guardrails
By performing multi-step surface passivation treatment on the highway guardrail low-chromium ferrite stainless steel, a dense passivation film is formed, which solves the problem of insufficient corrosion resistance in chloride-containing environments, significantly improves corrosion resistance and extends service life.
Patent Information
- Application Number
- CN202411988341.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-18
AI Technical Summary
Low-chromium ferrite stainless steel has insufficient corrosion resistance in chloride-containing environments, resulting in rust on the surface of the guardrail and reduced structural integrity, affecting road safety and service life.
A surface passivation method is adopted, including step-by-step grinding of stainless steel sheets with multiple mesh sandpaper, ultrasonic cleaning and soaking in nitric acid solution, to form a dense passivation film to improve corrosion resistance.
It significantly improves the corrosion resistance of low-chromium ferrite stainless steel, reduces corrosion current density and breakdown potential, extends service life and ensures the stability and safety of highway guardrails.
Smart Images

Figure CN119843264A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new metal materials and preparation thereof, and in particular relates to a surface passivation method for improving the corrosion resistance of low-chromium ferrite stainless steel used for highway guardrails. Background Art
[0002] Low-chromium ferritic stainless steel is widely used in many fields, especially in highway guardrail construction, due to its relatively good mechanical properties, welding convenience and outstanding cost-effectiveness. At the microstructural level, it is mainly composed of ferrite phase, and the chromium content is usually in the range of 10.5-30.0%. Compared with some stainless steel materials containing rare metals such as nickel, its cost is more acceptable and it has strong competitiveness in large-scale infrastructure applications.
[0003] However, with the increasing complexity of highway guardrail usage scenarios and the increasing requirements for service life, the problem of insufficient corrosion resistance of low-chromium ferritic stainless steel has become increasingly prominent. In natural environments, especially in environments containing chloride ions (Cl⁻), such as near the seaside or in areas where more snow-melting agents are used, due to its relatively low chromium content, it is difficult to form a sufficiently dense and stable passivation film to resist the erosion of corrosive media, resulting in a significant decrease in its corrosion resistance. This will not only cause rust and mottled spots on the surface of the guardrail, affecting its appearance, but will also gradually weaken the structural integrity of the guardrail, reduce its protective effectiveness for road safety, greatly shorten its expected service life, and increase the cost of frequent replacement and maintenance.
[0004] Although a variety of surface treatment technologies can be used to improve the corrosion resistance of metal materials, there is still a lack of surface passivation technology for low-chromium ferritic stainless steel in terms of improving its Cl⁻ corrosion resistance. An efficient, simple and economical surface passivation method is of great practical significance for giving full play to the advantages of low-chromium ferritic stainless steel in the field of highway guardrails, extending its service life and ensuring road traffic safety.
[0005] Traditional methods such as chemical nickel plating, chromate passivation, and phosphating treatment have problems such as unstable coating, complex process, serious pollution, and high cost, making them difficult to promote and apply on a large scale. In some literature studies, a passivation film can be formed on the surface of stainless steel by immersing stainless steel in a nitric acid solution of a certain concentration. These experiments usually specify process parameters such as the concentration range of nitric acid, the temperature and time of the passivation treatment. Compared with previous studies, the method used in this patent is specifically for low-chromium ferritic stainless steel for highway guardrails, and has been optimized to use the most suitable combination of concentration, temperature, and time. Under the premise of ensuring the passivation effect, the amount of nitric acid reagent used is reduced by optimizing the process parameters, and the processing cost is reduced. The operation process is simplified as much as possible to make the entire passivation process easier to control and implement. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes a surface passivation method for improving the corrosion resistance of low-chromium ferritic stainless steel for highway guardrails. The method has a relatively simple process and can significantly improve the corrosion resistance of stainless steel.
[0007] To achieve the above object, the present invention provides a surface passivation method, which comprises the following steps:
[0008] A surface passivation method for improving the corrosion resistance of low-chromium ferritic stainless steel for highway guardrails, wherein the constituent elements of the low-chromium ferritic stainless steel for highway guardrails are respectively as follows by mass percentage: 0<C≤0.030%, 0<Si≤0.45%, 0<P≤0.015%, 0<Mn≤1.20%, 11.50%≤Cr≤13.50%, 0<Ni≤0.60%, 0<N≤0.015%, 0.001%≤B≤0.003%, and the balance is Fe;
[0009] The surface passivation method comprises the following steps:
[0010] (1) The ferritic stainless steel sheet for highway guardrail is gradually polished from 120 mesh to 2000 mesh using sandpaper, and then ultrasonically cleaned with anhydrous ethanol with a purity of not less than 95% and blown dry;
[0011] (2) Soaking the stainless steel plate obtained in step (1) in a preheated nitric acid solution with a concentration of 1.6-2.0 mol / L and a temperature of 70-80°C for 0.5-1.5 h;
[0012] (3) The ferritic stainless steel plate for highway guardrail after being immersed in step (2) is taken out from the solution, and is washed with deionized water and alcohol and blown dry.
[0013] Furthermore, in step (1), the sandpaper grinding is performed starting from 120 mesh and then sequentially changing to 240 mesh, 400 mesh, 800 mesh, 1200 mesh and finally 2000 mesh sandpaper.
[0014] Furthermore, during the grinding process, each time the sandpaper is changed, the grinding direction needs to be 90° to the previous grinding direction.
[0015] Furthermore, in step (2), the nitric acid solution is preheated by placing the container containing the nitric acid solution in a constant temperature water bath for heating, and at the same time, a stirring device is provided in the nitric acid solution at a stirring rate of 50-100 r / min.
[0016] Furthermore, in step (3), the deionized water cleaning is performed by rinsing multiple times, with each rinsing time being no less than 30 seconds; the alcohol cleaning is performed by soaking for 1-2 minutes, then taking out and wiping dry with a non-woven fabric.
[0017] Furthermore, the specific steps of the surface passivation method are:
[0018] (1) The low-chromium ferrite stainless steel sheet for highway guardrail is subjected to surface grinding and cleaning treatment to obtain a treated sheet; specifically, the sheet is gradually polished using sandpaper starting from 120 mesh and then replaced in sequence with 240 mesh, 400 mesh, 800 mesh, 1200 mesh, and finally 2000 mesh, with the grinding direction of each change of sandpaper being 90° to the previous grinding direction, followed by ultrasonic cleaning for 3 min (ultrasonic frequency 40 kHz) with anhydrous ethanol having a purity of not less than 95%, then soaking and cleaning for 2 min, and finally drying with nitrogen (pressure 0.2-0.5 MPa, air flow velocity 5-10 m / s).
[0019] (2) Place the treated stainless steel plate in a preheated nitric acid solution for passivation reaction; soak the treated stainless steel plate in a 1.8 mol / L nitric acid solution preheated to 75°C for 1 h. The nitric acid solution is preheated in a constant temperature water bath. There is a stirring device in the container (stirring rate 50-100 r / min). The plate is slowly placed in to ensure complete immersion and the container is sealed to reduce volatilization. Ensure that the plate is in full contact with the solution when placed.
[0020] (3) Clean and post-process the plate after the passivation reaction; take out the stainless steel plate after soaking for 1 hour, rinse it with deionized water several times (each time for no less than 30 seconds), soak it in alcohol for 1-2 minutes, wipe it dry with non-woven cloth, and then place it in a dry and dust-free environment to dry naturally for 10-15 minutes before subsequent performance testing or use.
[0021] Compared with the prior art, the present invention has the following advantages and technical effects:
[0022] The surface passivation method for improving the corrosion resistance of low-chromium ferritic stainless steel for highway guardrails involved in the present invention has the characteristics of simple and efficient operation process, which greatly reduces the complexity and cost investment of process implementation, and after being treated by this method, the corrosion resistance of the material is significantly improved.
[0023] From the perspective of microscopic mechanism, the untreated low-chromium ferritic stainless steel for highway guardrails has a relatively low chromium content on its surface, which makes it difficult to spontaneously form a continuous, dense and highly stable passivation film structure in the natural environment, especially under conditions containing chloride ions. This results in a lack of an effective barrier between the metal matrix and the corrosive medium, resulting in a low self-corrosion potential (-231.74 mV vs. Ag / AgCl) and a relatively high corrosion current density (4.82×10⁻ 5 mA / cm²), and the breakdown potential is also low (195.21 mV vs. Ag / AgCl), indicating that it is very easy to undergo oxidation reaction and suffer local corrosion damage in a corrosive environment, seriously affecting the service life and structural integrity of the material.
[0024] The surface passivation method of the present invention effectively removes the original oxide layer, impurity particles and potential defect sites on the surface of stainless steel through carefully designed pretreatment steps, such as fine grinding with multi-mesh sandpaper and ultrasonic and immersion cleaning with anhydrous ethanol, providing an extremely clean and active uniform surface foundation for subsequent passivation treatment. In the passivation treatment stage, the best treatment process is to immerse the treated stainless steel sheet in a nitric acid solution of a specific concentration (1.6-2.0 mol / L) and preheated to the corresponding temperature (70-80°C) for 1 h, and use a constant temperature water bath to ensure the high stability of the solution temperature and a stirring device to ensure the uniformity of the solution concentration, so that the stainless steel surface and the nitric acid solution can undergo a precise and sufficient chemical reaction. In this process, nitrate ions undergo complex redox reactions with metal atoms such as iron and chromium on the surface of stainless steel, prompting the metal atoms to undergo moderate oxidation and forming a passivation film rich in chromium oxide, hydroxide and a small amount of iron oxide on the surface. The uniqueness of this passivation film lies in its high density, which can effectively block the direct contact between corrosive media such as chloride ions and the metal matrix; at the same time, the components such as chromium oxide inside it can significantly improve the surface potential stability through its own chemical stability and synergy with the metal matrix, thereby increasing the self-corrosion potential to -186.75 mV vs. Ag / AgCl, greatly reducing the thermodynamic tendency of the material to corrode. In addition, the passivation film also has good resistance to local breakdown, which greatly increases the breakdown potential to 756.03 mV vs. Ag / AgCl, effectively inhibiting the occurrence of local corrosion phenomena such as pitting. From a kinetic point of view, the presence of the passivation film greatly increases the energy barrier of the corrosion reaction, causing the corrosion current density to drop sharply to 7.01×10⁻ 6 mA / cm², significantly slowing down the rate of corrosion reaction.
[0025] In summary, the surface passivation method of the present invention comprehensively optimizes the structure and chemical composition of the stainless steel surface from a microscopic level, and effectively improves the corrosion resistance of low-chromium ferritic stainless steel for highway guardrails by forming a high-quality passivation film. It provides solid technical support for ensuring the stability and safety of highway guardrails during long-term use in complex environments. It has extremely important innovation and application value, and shows broad application prospects in the field of highway guardrails and other low-chromium ferritic stainless steel application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 X-ray diffraction patterns of low chromium ferritic stainless steel for highway guardrails before and after surface passivation.
[0028] Figure 2 Scanning electron microscope images of low chromium ferritic stainless steel for highway guardrail before and after surface passivation.
[0029] Figure 3 These are the electrochemical potentiodynamic polarization curves of low chromium ferritic stainless steel for highway guardrail before and after surface passivation in a 0.3wt.% NaCl environment. DETAILED DESCRIPTION
[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0031] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0032] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0033] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. It will be apparent to those skilled in the art that other embodiments may be derived from the present invention description. The present invention description and examples are exemplary only.
[0034] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0035] The present invention provides a surface passivation method for improving the corrosion resistance of low-chromium ferrite stainless steel for highway guardrails, which specifically comprises the following steps:
[0036] Step 1, plate pretreatment: the low chromium ferritic stainless steel plate for highway guardrail is gradually polished with sandpaper starting from 120 mesh, then replaced with 240 mesh, 400 mesh, 800 mesh, 1200 mesh and finally 2000 mesh, and the polishing direction of each change of sandpaper is 90° to the previous one, and then ultrasonically cleaned with anhydrous ethanol with a purity of not less than 95% for 3 min (ultrasonic frequency 40 kHz), then immersed and cleaned for 2 min, and finally blown dry with nitrogen (pressure 0.2-0.5 MPa, air flow speed 5-10 m / s).
[0037] Step 2, passivation reaction: Soak the treated stainless steel plate in a 1.5-4.0mol / L nitric acid solution preheated to 40-80℃ for 0.5-1.5 h. The nitric acid solution is preheated in a constant temperature water bath. There is a stirring device in the container (stirring rate 50-100 r / min). The plate is slowly placed in to ensure complete immersion and the container is sealed to reduce volatilization. Ensure that the plate is in full contact with the solution when placed.
[0038] Step 3, post-cleaning treatment: Take out the soaked stainless steel plate, rinse it with deionized water several times (each time for no less than 30 seconds), soak it in alcohol for 1-2 minutes, wipe it dry with non-woven cloth, and then place it in a dry and dust-free environment to dry naturally for 10-15 minutes before subsequent performance testing or use.
[0039] Example 1
[0040] This embodiment 1 provides a surface passivation method for improving the corrosion resistance of low-chromium ferrite stainless steel for highway guardrails, and the process includes the following specific steps:
[0041] (1) Plate pretreatment: The preparation percentages of low chromium ferritic stainless steel for highway guardrails are C: 0.02%, Si: 0.42%, Mn: 0.17%, P: 0.03%, Cr: 12.4%, Ni: 0.14%, B: 0.0018%, and the balance is Fe.
[0042] The low-chromium ferrite stainless steel sheet for highway guardrail is placed on a flat workbench, and 120-mesh sandpaper is used to polish in the same direction with uniform and moderate force to remove the initial oxide layer and rough impurities on the surface of the sheet. Subsequently, 240-mesh sandpaper is replaced, and the polishing direction is adjusted to 90° with the previous step, and polishing is continued to further refine the surface. In this way, 400-mesh, 800-mesh, 1200-mesh and 2000-mesh sandpapers are used for step-by-step polishing. Each time the sandpaper is replaced, the polishing directions are strictly ensured to be perpendicular to each other, ensuring that the surface flatness of the stainless steel sheet is gradually improved, and surface impurities and scratches are effectively removed. After polishing, the sheet is placed in an ultrasonic cleaning tank filled with anhydrous ethanol with a purity of not less than 95%, and the ultrasonic frequency is set to 40 kHz. Clean for 3 min, so that the ethanol can fully penetrate into the fine gaps and holes on the surface of the sheet to remove residual impurities. After ultrasonic cleaning, continue to use anhydrous ethanol to soak and clean for 2 minutes in the same container, then take out the plate and place it on a special drying workbench. Use a nitrogen spray gun, adjust the nitrogen pressure to 0.2-0.5 MPa, control the air flow speed at 5-10 m / s, and blow dry the plate to ensure that there is no moisture and ethanol residue on the surface of the plate, providing a clean surface foundation for subsequent passivation treatment.
[0043] (2) Passivation treatment: The pretreated stainless steel plate is placed on a special passivation treatment rack and prepared to be placed in a preheated nitric acid solution. The concentration of the nitric acid solution is 1.8 mol / L. A constant temperature water bath is used to preheat the glass container containing the nitric acid solution, and the water bath temperature is precisely controlled at 75°C. A stirring device is installed in the nitric acid solution container, and the stirring rate is set to 50-100 r / min to ensure the uniformity of the solution temperature and concentration. The operator wears protective gloves and goggles, and slowly places the stainless steel plate into the nitric acid solution to avoid splashing the solution. At the same time, ensure that the plate is completely immersed in the solution, and ensure that all surfaces of the plate are in full contact with the solution when placed. During the immersion process, the container is sealed to reduce the effect of solution volatilization on the concentration, so that the stainless steel plate can evenly undergo a passivation reaction with the nitric acid solution during the immersion process of 1 hour, forming a dense passivation film on the surface of the plate, thereby improving its corrosion resistance.
[0044] (3) Post-treatment: After the stainless steel plate is soaked in the nitric acid solution for 1 hour, use a special clamp to slowly remove it from the solution and immediately transfer it to the deionized water rinsing area. Use multiple rinses, each rinse time is not less than 30 seconds, to ensure that the residual nitric acid solution and reaction products on the surface of the plate are completely removed. After the deionized water rinse is completed, place the plate in a container filled with alcohol (such as industrial alcohol or analytical pure alcohol) and soak for 1-2 minutes to allow the alcohol to dissolve and remove any trace impurities that may remain. After soaking, use a clean non-woven cloth to gently wipe the surface of the plate to avoid damaging the passivation film. Finally, place the cleaned stainless steel plate in a dry, dust-free and well-ventilated environment to dry naturally for 10-15 minutes. After it is completely dry, subsequent performance testing can be carried out to prevent dust and other impurities from being contaminated during the drying process, affecting its corrosion resistance and appearance quality.
[0045] Example 2
[0046] The only difference between this embodiment and embodiment 1 is that the temperature of the nitric acid solution in step (2) is 50°C.
[0047] Example 3
[0048] The only difference between this embodiment and embodiment 1 is that the concentration of the nitric acid solution in step (2) is 3.6 mol / L.
[0049] Comparative Example
[0050] This comparative example only adopts step (1) in Example 1 for processing; after completion, subsequent steps (2) and (3) are not performed.
[0051] Relevant tests were performed on Example 1, Example 2, Example 3 and the comparative example in the present invention, and the specific test methods and results are as follows:
[0052] (1) Test method
[0053] X-ray diffraction analysis: It was conducted by a Rigaku SmartLab diffractometer. The current and voltage during the test were 40 kV and 150 mA, respectively, and the diffraction angle (2θ) was 20°-90°. The sample size used for the test was 10 mm × 10 mm × 4 mm. Before the test, the sample surface was polished with 240-2000 mesh sandpaper. The diffraction data obtained from the test was analyzed and calibrated using Jade 9 software.
[0054] Scanning electron microscope analysis: Zeiss Auriga Focused Ion Beam scanning electron microscope was used to observe the microstructure of low-chromium ferrite stainless steel for highway guardrails before and after surface passivation. For the samples used for scanning electron microscope analysis, the surface of the sample was first polished with 240-2000 mesh sandpaper, and then the surface was polished with 50nm silica suspension to remove surface stress. The polished samples were cleaned with anhydrous ethanol for use.
[0055] Electrochemical potentiodynamic polarization curve test: The surface of the sample used for electrochemical testing was polished with 240-2000 mesh sandpaper in turn to make the surface state of the sample consistent. The electrochemical test was completed using an Ametek Princeton VersaSATA 3F electrochemical workstation, using a typical three-electrode system in a 0.3 wt. % NaCl solution. The reference electrode was Ag / AgCl (saturated KCl), the auxiliary electrode was a carbon rod, and the working electrode was the experimental sample. The back of the working electrode was connected to the copper wire with conductive glue and then sealed with epoxy resin. The scan rate of the potentiodynamic polarization curve was 1 mV / s.
[0056] (2) Test results
[0057] like Figure 1 The X-ray diffraction results of Example 1 and the comparative example of the low chromium ferritic stainless steel for highway guardrails before and after surface passivation are shown. It can be seen that the ferritic stainless steel presents a body-centered cubic (BCC) crystal structure in both Example 1 and the comparative example. In Example 1, the intensity and position of the diffraction peaks are compared with the comparative example, and there is no obvious shift or new phase generation, indicating that the passivation treatment does not change the crystal structure type of the stainless steel.
[0058] like Figure 2 Shown are the microstructural observation results of the comparative example and the embodiment of the low chromium ferrite stainless steel for highway guardrail in the present invention. Figure 2 (a) and (c) are comparative examples. The microstructure of stainless steel shows typical ferrite characteristics, with some holes and irregular shapes on the surface. Figure 2 (b) and (d) are the results of Example 1. The holes and irregular shapes on the surface are reduced, and the surface is relatively smoother. This may be because the passivation treatment forms a protective film on the surface, which improves the surface microstructure.
[0059] like Figure 3The polarization curve test results of the low-chromium ferritic stainless steel for highway guardrails of the present invention are shown in the comparative example, example 1, example 2 and example 3. From the specific data of the polarization curve, before treatment (comparative example), the self-corrosion potential is -221.74 mV vs. Ag / AgCl. This lower self-corrosion potential indicates that in the natural environment, untreated stainless steel materials are prone to corrosion reactions because their electrode potential is relatively more negative and they are more likely to lose electrons and be oxidized. Its corrosion current density is 4.82×10⁻ 5 mA / cm², a higher corrosion current density means that during the corrosion process, a larger current passes through a unit area, reflecting that the corrosion reaction proceeds more rapidly. In addition, the breakdown potential of untreated stainless steel is 195.21 mV vs. Ag / AgCl. The lower breakdown potential indicates that the material may undergo local corrosion damage at a lower potential, such as pitting. After being treated with the surface passivation method of the present invention (Example 1, Example 2, Example 3), the self-corrosion potential, corrosion current density and breakdown potential are all improved. Among them, Example 1 exhibits the best corrosion resistance. The self-corrosion potential is increased to -186.75 mV vs. Ag / AgCl. The increase in the self-corrosion potential means that the treated stainless steel material has a significantly reduced tendency to corrode under the same environment, and the electrode potential becomes relatively more positive and less susceptible to oxidation. The corrosion current density is reduced to 7.01×10⁻ 6 mA / cm², this data shows that after passivation treatment, the corrosion current per unit area is greatly reduced, the rate of corrosion reaction is effectively controlled, and the corrosion process becomes very slow. More significantly, the breakdown potential is increased to 756.03 mV vs. Ag / AgCl. The high breakdown potential indicates that local corrosion damage will occur only when the material experiences a higher potential, which fully demonstrates the excellent effect of the surface passivation method of the present invention in inhibiting local corrosion of stainless steel.
[0060] Table 1 Corrosion kinetic parameters of the comparative example and embodiment 1, embodiment 2 and embodiment 3 of the present invention
[0061]
[0062] In summary, it can be clearly seen from these specific data of the polarization curve test results that the surface passivation method of the present invention greatly improves the corrosion resistance of low chromium ferritic stainless steel for highway guardrails, thereby ensuring the stability and safety of highway guardrails during long-term use.
[0063] The above-mentioned Embodiment 1, Embodiment 2, and Embodiment 3 are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solution of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A surface passivation method for improving the corrosion resistance of low-chromium ferrite stainless steel for highway guardrails, characterized in that: The constituent elements of the low chromium ferrite stainless steel for highway guardrail are as follows by mass percentage: 0<C≤0.030%, 0<Si≤0.45%, 0<P≤0.015%, 0<Mn≤1.20%, 11.50%≤Cr≤13.50%, 0<Ni≤0.60%, 0<N≤0.015%, 0.001%≤B≤0.003%, and the balance is Fe; The surface passivation method comprises the following steps: (1) The ferritic stainless steel sheet for highway guardrail is gradually polished from 120 mesh to 2000 mesh using sandpaper, and then ultrasonically cleaned with anhydrous ethanol with a purity of not less than 95% and blown dry; (2) Soaking the stainless steel plate obtained in step (1) in a preheated nitric acid solution with a concentration of 1.6-2.0 mol / L and a temperature of 70-80° C. for 0.5-1.5 h; (3) The ferritic stainless steel plate for highway guardrail after being immersed in step (2) is taken out from the solution, and is washed with deionized water and alcohol and blown dry.
2. The surface passivation method according to claim 1, characterized in that: In step (1), the sandpaper grinding is started from 120 mesh, and then replaced in sequence with 240 mesh, 400 mesh, 800 mesh, 1200 mesh, and finally 2000 mesh sandpaper for step-by-step grinding.
3. The surface passivation method according to claim 2, characterized in that: During the grinding process, each time the sandpaper is changed, the grinding direction must be 90° to the previous grinding direction.
4. The surface passivation method according to claim 3, characterized in that: In step (2), the nitric acid solution is preheated by placing the container containing the nitric acid solution in a constant temperature water bath for heating. At the same time, a stirring device is provided in the nitric acid solution at a stirring rate of 50-100 r / min.
5. The surface passivation method according to claim 4, characterized in that: In step (3), the deionized water cleaning is performed by rinsing multiple times, with each rinsing time being no less than 30 seconds; the alcohol cleaning is performed by soaking for 1-2 minutes, then taking out and wiping dry with non-woven cloth.
Citation Information
Patent Citations
Production technology for ferrite stainless-steel grinding object with low cost and high corrosion resistance capability
CN101676435A
Metal surface corrosion resistance treatment method
CN108546943A
Super 13Cr stainless steel surface pickling treatment method
CN113737187A
Groove type pickling process for 022Cr11Ti ferritic stainless steel hot-rolled coiled and cut plate
CN115369409A
Method for passivating cold-forged component made from ferritic stainless steel
JP2008266677A